Two new species of Fulvifomes (Hymenochaetales, Basidiomycota) from South America - Jian Chen; Yuan Yuan; Kai-Yue Luo; Josef Vlasák (MycoKeys, 2025)
Two new species of Fulvifomes are described from specimens collected in South America (Ecuador and Bolivia) based on morphological and molecular evidence. The species Fulvifomes bolivianus is characterized by perennial, pileate, solitary basidiocarp; ungulate pilei; olivaceous, encrusted, rough, concentrically sulcate, irregularly cracked pileal surface; umber and glossy pore surface; circular pores measuring 7–8 per mm; thick and entire dissepiments; a dimitic hyphal system; and subglobose basidiospores measuring 4.7–5.4 × 4–4.5 µm. Fulvifomes fragilis is characterized by annual, pileate, imbricate basidiocarps; curry yellow to yellowish brown pileal surface; yellowish brown and narrow pileal margin; yellow and rugged pore surface; circular to elliptical pores measuring 5–6 per mm; thick and entire dissepiments; a dimitic hyphal system; and broadly ellipsoid basidiospores measuring 3.9–5.1 × 3–3.7 µm. Phylogenetically, the two new species formed two distinct lineages in the Fulvifomes clade based on internal transcribed spacer (ITS) and nuclear-encoded large subunit rRNA gene (nLSU) sequences. The differences between the new species and morphologically similar and phylogenetically related species are also discussed.